2018
DOI: 10.5430/jnep.v8n11p50
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorder: Risk factors and coping strategies among nurses

Abstract: Background: It is established that nurses suffer from varying degrees of Musculoskeletal Disorders (MSD) at different regions of their body, which results in frequent loss of work days. Aim of study is to identify the risk factors for developing musculoskeletal disorder and to determine the coping strategies to reduce their frequency. Methods: This study was conducted in the Outpatient Departments (OPDs), intensive care units of University Hospital and also from the nursing schoolof the Faculty of Nursing, Ale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The prevalence of work-related MSD among nurses varies between studies. Salama and Eleshenamie [14] studied the risk factors of MSD and coping strategies among 300 nurses in outpatient departments and intensive care units. They found that a high proportion of nurses reported MSD (99.0%) during the last year.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of work-related MSD among nurses varies between studies. Salama and Eleshenamie [14] studied the risk factors of MSD and coping strategies among 300 nurses in outpatient departments and intensive care units. They found that a high proportion of nurses reported MSD (99.0%) during the last year.…”
Section: Introductionmentioning
confidence: 99%
“…Kod medicinskih tehničara u Italiji je nađeno da je prevalenca bola u donjem dijelu leđa 49%, a u Brazilu je 45% [5]. U ambulantnim uslovima u Maleziji prevalenca je 89% [6], a u jedinicama intenzivnog liječenja u Egiptu 73% [7] ili Turskoj 84% [8].…”
Section: Uvodunclassified
“…(2018) study among nurses in Egypt, which revealed that the nurses were of childbearing age and had two pregnancies in the last two years. 80 Further evidence was also found in Al-Hadidi et al (2020) cross-sectional study developed among female nurses of childbearing age since lower back pain is considered the most common WMSD among female healthcare workers. 66 Also, most of the nurses who participated in the study at the GPHC had a diploma in nursing, and the highest level of education attained by the nurses was a Bachelor"s degree in nursing.…”
Section: Years Of Employmentmentioning
confidence: 74%
“…The coping strategies statistically significant were nurses using different parts of their bodies during nursing procedures (34%) and change of posture (30%). 80 Several reports have shown that MSD is one of the most occupational health problems seen in society among healthcare workers, particularly nurses, with a frequency of 40% to 90%, which is even three or four times the general population. 81 REBA survey to assess posture, and the study findings showed that the waist was the most prevalent MSD found among the operating room personnel and the nursing personnel with 46.7% and 56.7%, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%